2015
DOI: 10.1002/2014je004781
|View full text |Cite
|
Sign up to set email alerts
|

The Fe snow regime in Ganymede's core: A deep‐seated dynamo below a stable snow zone

Abstract: Ganymede shows signs of a present-day magnetic field, whose origin is thought to be in its core. The Fe snow regime has been suggested to be vital in Ganymede's history. In this regime, Fe crystals first form at the core-mantle boundary and later settle to the deeper core due to their higher density (Fe snow). A stable chemical gradient arises within the liquid of the snow zone. Below the snow zone the Fe particles remelt. We propose that the remelting of Fe in the deeper, entirely liquid core initiates compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 84 publications
2
65
0
Order By: Relevance
“…The inverse will happen near the CMB: denser Fe will snow downwards in the core and leave the outermost liquid richer in S. If convection is not vigorous enough, the stratification could stabilize the core into compositionally distinct layers, in which convection occurs only in the steadily shrinking wellmixed central zone. This might quell dynamo activity and end Mars' magnetic era (Weiss et al 2002;Williams and Nimmo 2004), like what may be occurring in Ganymede (Rückriemen et al 2015).…”
Section: Compositionmentioning
confidence: 91%
“…The inverse will happen near the CMB: denser Fe will snow downwards in the core and leave the outermost liquid richer in S. If convection is not vigorous enough, the stratification could stabilize the core into compositionally distinct layers, in which convection occurs only in the steadily shrinking wellmixed central zone. This might quell dynamo activity and end Mars' magnetic era (Weiss et al 2002;Williams and Nimmo 2004), like what may be occurring in Ganymede (Rückriemen et al 2015).…”
Section: Compositionmentioning
confidence: 91%
“…This so-called iron snow regime has already been suggested to apply to the present cores of Ganymede (Hauck et al 2006;Christensen 2015;Rückriemen et al 2015) and Mercury (Chen et al 2008;Vilim et al 2010;Wicht and Heyner 2014). It has also been suggested that Mars' core may enter the iron snow regime (Stewart et al 2007) and that the lunar core may have gone through an iron snow episode (Zhang et al 2013;Laneuville et al 2014).…”
Section: Iron Snow Regimementioning
confidence: 91%
“…Thus, in the snow zone, the liquidus becomes collinear with the core temperature and reverses its slope, so that the liquidus temperature increases with increasing depth. The increase of the liquidus with depth in the snow zone is inevitably accompanied by a decrease in the sulfur concentration with depth, which implies the presence of a stable chemical gradient across the snow zone (Hauck et al 2006;Williams 2009;Rückriemen et al 2015). Usselman (1975), Boehler (1993), Boehler (1996), Fei et al (1997Fei et al ( , 2000, Shen et al (1998), Alfè et al (2002b), Campbell et al (2007), Chudinovskikh and Boehler (2007), Morard et al (2007), and Stewart et al (2007).…”
Section: Iron Snow Regimementioning
confidence: 99%
See 2 more Smart Citations